Dimethyl Sulfoxide Promotes the Multiple Functions of the Tumor Suppressor HLJ1 through Activator Protein-1 Activation in NSCLC Cells - Wang, Chi-Chung; Lin, Sheng-Yi; Lai, Yi-Hua; Liu, Ya-Jung; Hsu, Yuan-Lin; Chen, Jeremy J. W. (PLOS ONE, 2012)
Background Dimethyl sulfoxide (DMSO) is an amphipathic molecule that displays a diversity of antitumor activities. Previous studies have demonstrated that DMSO can modulate AP-1 activity and lead to cell cycle arrest at the G1 phase. HLJ1 is a newly identified tumor and invasion suppressor that inhibits tumorigenesis and cancer metastasis. Its transcriptional activity is regulated by the transcription factor AP-1. However, the effects of DMSO on HLJ1 are still unknown. In the present study, we investigate the antitumor effects of DMSO through HLJ1 induction and demonstrate the mechanisms involved. Methods and Findings Low-HLJ1-expressing highly invasive CL1–5 lung adenocarcinoma cells were treated with various concentrations of DMSO. We found that DMSO can significantly inhibit cancer cell invasion, migration, proliferation, and colony formation capabilities through upregulation of HLJ1 in a concentration-dependent manner, whereas ethanol has no effect. In addition, the HLJ1 promoter and enhancer reporter assay revealed that DMSO transcriptionally upregulates HLJ1 expression through an AP-1 site within the HLJ1 enhancer. The AP-1 subfamily members JunD and JunB were significantly upregulated by DMSO in a concentration-dependent manner. Furthermore, pretreatment with DMSO led to a significant increase in the percentage of UV-induced apoptotic cells. Conclusions Our results suggest that DMSO may be an important stimulator of the tumor suppressor protein HLJ1 through AP-1 activation in highly invasive lung adenocarcinoma cells. Targeted induction of HLJ1 represents a promising approach for cancer therapy, which also implied that DMSO may serve as a potential lead compound or coordinated ligand for the development of novel anticancer drugs.